2018
DOI: 10.1111/iju.13767
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the preoperative serum albumin : globulin ratio after radical nephroureterectomy for upper tract urothelial carcinoma

Abstract: A low albumin : globulin ratio is an independent predictive factor associated with poor prognosis in upper tract urothelial carcinoma patients treated with radical nephroureterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Several studies have reported on the association of hypoalbuminemia with poor prognosis in patients with UC ( Table 5) (49,68,72,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). The cutoff value of albumin varies from 2 to 4 mg/L, although it is normally around 3.5 mg/L.…”
Section: Albumin and Albumin-globulin Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the association of hypoalbuminemia with poor prognosis in patients with UC ( Table 5) (49,68,72,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). The cutoff value of albumin varies from 2 to 4 mg/L, although it is normally around 3.5 mg/L.…”
Section: Albumin and Albumin-globulin Ratiomentioning
confidence: 99%
“…However, considering the limited number of studies, the utility of this combination remains to be established. Recent studies have reported on the prognostic effect of AGR in patients with UC (85)(86)(87)(88)(89)(90)(91).…”
Section: Albumin and Albumin-globulin Ratiomentioning
confidence: 99%
“…Clinicopathological factors that serve as prognostic factors for UTUC [5][6][7][8][9][10][11][12][13][14][15] include sex [5], age [6], tumor size [7,8], ureteral involvement [9], and body mass index [10], as well as laboratory markers [11][12][13][14][15] such as the neutrophil-to-lymphocyte ratio [11,12], albumin [13], hemoglobin [14], and the prognostic nutritional index [15]. On the other hand, the AGR has been reported as a useful biomarker in various malignancies [16][17][18][19][20][21][22][23][24][25][26], including urological cancers [20][21][22][23][24][25][26]. However, the significance of the AGR as a prognostic marker for UTUC has not been fully investigated [23][24]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the AGR has been reported as a useful biomarker in various malignancies [16][17][18][19][20][21][22][23][24][25][26], including urological cancers [20][21][22][23][24][25][26]. However, the significance of the AGR as a prognostic marker for UTUC has not been fully investigated [23][24][25][26]. For example, a study of a Chinese cohort of 187 operable patients with UTUC [23] demonstrated that AGR < 1.45 is an independent risk factor for poorer CSS and OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation